Abdominal Actinomycetoma With Lymphnode Involvement - Damisetty Rajetha; Janaki C; Sentamilselvi G; Janaki V R (Wolters Kluwer Medknow Publications, 2004)
Actinomycotic mycetoma of the anterior abdominal wall with inguinal lymphnode involvement, an exceedingly rare entity is described here with mycological histological features. Remarkable therapeutic response was noted with Welsh regimen.